New proof of Erdös—Turan’s theorem - Yudin, A. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. А. Юдин. Новое доказательство теоремы Эрдёша—Турана A. Judinas. Erdiošo—Turano teoremos naujas įrodymas